The evolving epidemiology of rotavirus gastroenteritis in central Portugal with modest vaccine coverage - Rodrigues, Fernanda; Iturriza-Gómara, Miren; Marlow, Robin; Gray, Jim; Nawaz, Sameena; Januário, Luís; Finn, Adam (Journal of clinical virology, 2013)
Rotavirus (RV) vaccines have been available on the private market in Portugal since 2006, with an estimated coverage rising from 16 to 42% between 2007 and 2010. To assess trends, surveillance of children presenting with acute gastroenteritis (AG) to a large paediatric emergency service (ES) in the central region of Portugal was conducted yearly during the winter–spring seasons. Stool samples, collected throughout five epidemic seasons (January–June, 2006 to 2010) from children ≤36 months of age attending the ES with AG, were tested for RV by immunochromatographic rapid test and positive samples were genotyped. A total of 6145 AG cases were identified: 1956 (32%) provided a stool sample (range: 28% in 2008–37% in 2009). The proportion of AG subjects who tested positive for RV fluctuated over the five surveillance seasons (49%, 39%, 25%, 26% and 39%, respectively) as did the distribution of co-circulating RV genotypes. There were no consistent changes in seasonality or age distribution and the proportion of admitted AG subjects who tested RV-positive did not show progressive trends over time. Our results demonstrate fluctuations in RVAG incidence with no clear progressive trends or seasonal RV shifts among our surveillance subjects over five years, in the context of limited rotavirus vaccine coverage. Significant annual changes in genotype distributions were detected. Higher vaccine coverage may be necessary than at present for consistent impact on disease.